(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Labour welfare is an important part of labour-management relations. Labour welfare is an extension of the term welfare and its application to labour management. Welfare means fairing and doing well. There are many positive point of labour welfare such as Improvement in labour-management relations, increase in the efficiency and income, high morale of workers, worker satisfaction and increase effectivness, creation of permanent labour force, improvement in the mental and moral health etc. This paper tells about nature, definition, scope etc. of labour welfare.